St Pius V (1504–72) and Sta Caterina De' Ricci (1523–90): Two Ways of Being a Saint in Counter-Reformation Italy. (4th January 2016) - Preston, Patrick
Abstract : Recent students of the Counter-Reformation in Italy have not neglected the subject of sanctity. For example, one such student, Peter Burke, has dealt with it in a general and theoretical way, while others, such as Gabriella Zarri, have concentrated on certain classes of saints, in her case female saints and beatae . Scholars, however, whose interests are in the particular rather than the general, have tended to prefer to study the lives and times of individual saints, and the perceptions of them by their contemporaries. A different approach altogether has been to study a particular aspect of sanctity, such as hagiography or canonization. Similarly, some scholars have concentrated on the salient aspects of the contribution that particular individuals made to the work of the Church militant, for example church reform in the case of Charles Borromeo or the repression of heresy in that of Michele Ghislieri.